(untitled) (Altre Modernità, 2024)
In comparison with other Italian cities, perhaps with the only exception of Rome, Milan is the urban space most often represented in films. A metropolis closely resembling the great European and extra-European great urban sprawl and a place of industrialization and efficiency, over time the city has been made into a space of migration, first from Southern Italy, then from other lands that have suddenly become very near. Documentary filmmaking has provided many interesting, seminal, sometimes poetic, accounts of this process. In doing so, it has connected to a well-rooted if little-known tradition. This text, close in its genesis to the birth of the documentary film archive Docucity. Documenting the city, selects some representative texts where the “new Italians” leave important traces in the fabric of the city.